Políticas educacionais e os espaços físicos para a prática pedagógica em educação física na rede municipal de Campina Grande-PB: entre o real e o ideal - Nascimento, Maria do Socorro (2012)
The present study aims to analyze the educational policy of the scholar Physical Education in Campina Grande-PB and the reality of the working conditions of the teachers of this school subject, from a fundamental aspect of the Pedagogical Practice: the physical space of class. Initially, this study presents a discussion about the relation established between social public policy in the Brazilian state, taking as a reference the local educational policy, and it proceeds dialoguing with the ways of thinking the Physical Education represented in the pedagogical approaches for its teaching and its difficult dialogue with the physical space. This is a qualitative, descriptive and documental research and it was performed in four public schools from a Municipal Education System in the referred city. In order to achieve the objectives and aiming to contribute with the discussions about the educational policy to Physical Education in the scholar context, it was used as instrument of data collection, semi-structured interviews with the principals and the Physical Education teachers of the four schools and also with the Physical Education coordinator of the city. This study concludes that, despite the significant progress occurred in the methodological approaches of the area, there is a difference between them, the ideal and the educational reality, especially in the physical spaces of class. This difference can be characterized as one of the reasons to the deterioration of the teaching work conditions suffered by the teachers of this area. Based on the reality data, this study points out the indicators for this policies, in the perspective to show possible elements of transformation in the work structure of the classes and also overcome the poor working conditions identified.